Increasing temperature and flow management alter mercury dynamics in East Fork Poplar Creek. Issue 8 (23rd August 2021) - Brooks, Scott C.; Miller, Carrie L.; Riscassi, Ami L.; Lowe, Kenneth A.; Dickson, Johnbull O.; Schwartz, Grace E.
Abstract: East Fork Poplar Creek (EFPC) is a mercury (Hg) contaminated creek in east Tennessee, USA. Stream restoration activities included the initiation of a flow management programme in 1996 in which water from a nearby lake was pumped to the head of the creek. We conducted regular water sampling for 2 years along the length of EFPC during active flow management and for 5 years after flow management stopped. Total Hg and total monomethylmercury (MMHg) concentration and flux decreased in the uppermost reaches of EFPC that were closest to the point of water addition. Most water quality parameters, including DOC concentration, remained unchanged after flow management termination. Nevertheless, SUVA254, a measure of dissolved organic matter (DOM) composition, increased and coincided with increased dissolved Hg (HgD ) concentration and flux and decreased Hg solid‐water partitioning coefficients throughout EFPC. Higher SUVA254 and HgD concentration have potential implications for bioavailability and MMHg production. Total and dissolved MMHg concentrations increased in lower reaches of EFPC after the end of flow management and these increases were most pronounced during spring and early summer when biota are more susceptible to exposure and uptake. A general warming trend in the creek after active flow management ended likely acted in concert with higher HgD concentration to promote higher MMHg concentration. Total and dissolved MMHg concentrations were positively correlated with water temperature above a threshold value of 10°C. Concentration changes for Hg and MMHg could not be accounted for by changes in creek discharge that accompanied the cessation of flow management. In addition to the changing DOM composition in‐stream, other watershed‐scale factors likely contributed to the observed patterns, as these changes occurred over months rather than instantaneously after flow management stopped. Nevertheless, similar changes in MMHg have not been observed in a tributary to EFPC. Abstract : Changing flow management practises and increasing temperature in a low‐order stream resulted in changes to mercury and methylmercury concentrations and loading. These changes resulted from a combination of in‐stream and broader climate‐scale factors affecting solid‐water partitioning and mercury methylation.